ANALISIS STRATEGI PELAYANAN JAMA’AH HAJI KANTOR KEMENTERIAN AGAMA KABUPATEN SOLOK SELATAN - Fajril Wahdi; Ariyun Anisah, Jon Konedi, Rusdi Fauzan (Adisam Publisher, 2023)
This research is motivated by the unsatisfactory service provided by the PHU Section of the Office of the Ministry of Religion in Solok Selatan district. The problem is the lack of resources in managing administration, inadequate facilities such as weak internet network, and scattered congregational documents. The research objective is to find out how the service strategy is implemented in the Office of the Ministry of Religion of South Solok Regency. This type of research is field research that is qualitative in nature, data collection techniques are carried out through interviews, observation, and documentation, the data that has been collected is then analyzed following the stages of data collection, data reduction, data presentation, and the final stage is drawing conclusions. The results of this study indicate that the Office of the Ministry of Religion of South Solok Regency has carried out services in accordance with the service concept, namely attitude, attention, action, ability, appearance, accountability. Apart from that the strategy implemented is to provide good, comfortable, transparent, and free service as well as the ability to understand the character of each jama'ah, through providing comfort and providing valid information, is one form of service performed, besides that attitude friendly and polite, and responsibility is one of the strategies in providing services to prospective pilgrims.